Pangkalpinang Menuju Kota Kreatif (Sebuah Kajian Pengembangan Ekonomi Kreatif Di Kota Pangkalpinang) - Nurwasya Nurwasya; Ria Atlantika; Marlina Safitri; Karmawan Karmawan; Ryand Daddy Setyawan (Universitas Bangka Belitung, 2022)
This study describes the Development of the Creative Economy in Pangkalpinang City, based on a survey of 92 Creative Industry Business Actors in Seven Districts in Pangkalpinang City. The approach used in this research is qualitative which describes and analyzes descriptively. In addition, this research is also analytical descriptive in nature because the research is not only limited to descriptions of the object of study but also analyzes how creative economic policy models innovate. As for data processing using the following methods: The types of data used in this study are primary data and secondary data. Primary data collection was carried out using survey techniques through interviews and submission of questionnaires to Pangkalpinang City officials, creative economy experts, and creative economy industry players in the fashion, culinary, craft sub-sectors. Secondary data is supporting data from primary data obtained from related agencies such as the Central Bureau of Statistics (BPS) of Pangkalpinang City, the Tourism Office of Pangkalpinang City, the Office of Industry of Pangkalpinang City, previous studies, and other relevant literature. The results are based on data from 17 sub-sectors of the creative economy, it is obtained that the culinary sub-sector is the most dominant for development in Pangkalpinang City.